Hybrid Simulation for Modeling Healthcare-associated Infections: Promising But Challenging. (31st August 2020) - Nguyen, Le Khanh Ngan; Megiddo, Itamar; Howick, Susan
Abstract: Healthcare-associated infections (HAIs) are a major public health problem as they pose a serious risk for patients and providers, increasing morbidity, mortality, and length of stay, as well as costs to patients and the health system. Prevention and control of HAIs has, therefore, become a priority for most healthcare systems. Systems simulation models have provided insights into the dynamics of HAIs and help to evaluate the effect of infection control interventions. However, as each systems simulation modeling method has strengths and limitations, combining these methods in hybrid models can offer a better tool to gain complementary views on, and deeper insights into HAIs. Hybrid models can, therefore, assist decision-making at different levels of management, and provide a balance between simulation performance and result accuracy. This report discusses these benefits in more depth but also highlights some challenges associated with the use of hybrid simulation models for modeling HAIs. Abstract : Hybrid simulation for modeling infections is promising, as it can help gain deeper insights, assist decision-making at different management levels, and provide a balance between simulation performance and result accuracy, yet challenging to adopt without comprehensive theoretical and technical guidance.